Easily Multiplexable Immunoplatform to Assist Heart Failure Diagnosis through Amperometric Determination of Galectin-3 - Piguillem Palacios, Sofía Viviana (2020)
This work reports the first electrochemical immunoassay involving magnetic microbeads (MBs) for the determination of galectin-3 (Gal-3), a β-galactosidase-binding lectin that acts as mediator of heart failure (HF). MBs-captured sandwich-type immune complexes and amperometric detection at disposable screen-printed carbon electrodes were used. The immunoplatform showed a detection limit of 8.3 pg mL−1, good reproducibility, and excellent selectivity. The endogenous concentration of Gal-3 in human plasma from HF patients was determined with results in agreement with those obtained using ELISA. The multiplexing feasibility of the developed immunoplatform was demonstrated for the simultaneous determination of Gal-3 and N-terminal pro-brain natriuretic peptide (NT-proBNP).